The Public Health Importance of Monitoring Surface Water, Soil, Air, Biological Monitoring and Sustainable Mining - Dragičević, Igor; Jovanović, Verica (Napredak, 2024)
Modern technological advancements in mining involve the implementation of environmental standards and protective measures that significantly contribute to preserving natural resources and preventing potentially harmful impacts on the environment. These advancements enable early identification and minimisation of risks.The mining industry plays a vital role in the economic development of society while simultaneously adhering to strategies for environmental preservation and public health protection. This is achieved through modern methods for monitoring environmental parameters and population health. Mining and geological exploration may lead to the presence of potentially toxic elements (PTEs), which in certain concentrations across various environmental media pose challenges to both the environment and human health. Environmental monitoring is a crucial strategy for achieving sustainable mining. Sustainable mining development through effective monitoring of water, soil, air, and biological indicators in mining areas ensures the preservation of ecological balance and public health in regions where mineral exploitation occurs.
Keywords: mining; monitoring; surface water; soil; air; bio-monitoring